A Theoretical Study of Some Unsaturated Properties for Different Soils (Journal of University of Babylon for Engineering Sciences, 2018)
Soil–water characteristic curves (SWCC) can be defined as the relationship between the water content and suction of an unsaturated soil. It considered a basic relation to explanation of the engineering behaviour of unsaturated soil such as hydraulic conductivity and shear strength, So the study of SWCC is useful to reduce the time and cost of unsaturated soil testing for different engineering purposes. An approach model has been used to predict the SWCC for different soils. The influence of the soils on SWCC shape, the unsaturated hydraulic conductivity and shear strength parameters have been studied in this paper using mathematical models. The results of SWCC show that suction of clay soil is bigger than sandy soil, while the clayey silt soils exhibit an intermediate behaviour at same water content. The values of unsaturated shear strength are increasing while the unsaturated hydraulic conductivity is decreasing with increasing soil suction. This behaviour of the last two parameters with soil suction should be taken in consideration for engineering purposes.